Produção de hidrogel contendo óleo essencial de coriandrum sativum L. (coentro) com efeito sobre candida albicans envolvida com infecções da cavidade bucal - Barbosa, David Henrique Xavier (2023)
Objective: To produce a hydrogel containing essential oil (EO) from C. sativum L. and to evaluate the antifungal effect on Candida spp. involved with oral cavity infections, as well as verify the toxicological profile of this product. Methods: The chemical composition of the EO of C. sativum L. was identified by Gas Chromatography Coupled to the Mass Spectrometer, in addition, the incorporation of the EO to the hydrogel was verified by Infrared Spectroscopy by Fourier transform. Regarding the in vitro assays, the antifungal activity of the hydrogel containing EO was evaluated through the fungal susceptibility test, as well as the ability of the EO to reduce the metabolic activity of the buccal multispecies biofilm. The interference of the essential oil of C. sativum L. on the fungal micromorphology was also evaluated. Regarding the toxicological profile of the EO, the cytotoxicity test was carried out in human erythrocytes from human peripheral blood and cytotoxicity in keratinocytes of the HaCaT lineage by the MTT method. With regard to in vivo assays, an evaluation of genotoxicity was carried out in a test of micronucleated erythrocytes from peripheral blood of mice and an evaluation of toxicity in keratinized oral mucosa of rats. Results: The major components characteristic of this EO were described, such as: 2-decen-1-ol (22.42%), dec-(2E)-enal (19.31%) and 1,6-octadien-3-ol (13.41% ). In addition, the incorporation suggested by perpetuation of EO bands and interaction of EO with hydrogel molecules with change in band intensity was noted. With regard to in vitro assays, the hydrogel at a concentration of 20 mg/mL was able to form an inhibition halo above 28 mm. This EO at a concentration of 1600 μg/mL also showed the ability to reduce the metabolic activity of oral multispecies biofilm by 37% (p<0.0001). Furthermore, EO at concentrations related to Minimum Inhibitory Concentration (MIC) (62.5 μg/mL) and MICx2 (125 μg/mL) was able to reduce the frequency of pseudohyphae and modify the structure of blastoconidia. Regarding the toxicity related to the hemolytic activity of the EO, a CH50 higher than MICx4 (250 μg/mL) was pointed out. Furthermore, EO at concentrations of 150 and 300 μg/mL causes inhibition of keratinocyte cell viability and its IC50 was 60.13 ± 2.02 μg/mL. With regard to genotoxicity, treatment with a single dose of 20 mg/mL (5 mg/kg) of EO of C. sativum L. did not stimulate an increase in the number of micronuclei (16.40 ± 1.1). Finally, the formulation proved to be safe for use in keratinized mucosa of rats at a concentration of 20 mg/mL. Conclusions: The EO from C. sativum L. showed characteristic chemical constituents and was successfully incorporated into the hydrogel, showed antifungal activity seen in an inhibition halo and morphological changes in Candida albicans, in addition to reducing the metabolic activity of an oral multispecies biofilm. Furthermore, it was shown to be cytotoxic for human erythrocytes, however it was tolerable for HaCaT keratinocyte cells and was not genotoxic in a test with mice, as well as it is safe for use in keratinized oral mucosa of rats. These results will make it possible to carry out a phase I and II clinical trial with the purpose of making this therapeutic option available in the treatment of fungal infections.